Simplified Analysis and Validation of a Two-switch Flyback Converter - Virot Wuti; Chanin Bunlaksananusorn; Siripan Trakuldit; Kaweewat Tattiwong; Amata Luangpol; Alisala Taylim (My University, 2024)
This paper presents a simplified analysis and validation of a two-switch flyback converter. When parasitic components, i.e. the MOSFET’s output capacitance and transformer’s leakage inductance, are neglected, circuit analysis of the two-switch flyback converter is greatly simplified and derivation of the converter equations becomes straightforward. The validity of the derived equations, which are useful for the converter design, is confirmed by simulation and experimental results.
Keywords: Advanced DC-DC Converters; Silicon Carbide Semiconductor Technologies; Induction Heating and Inverter Technology